2017
DOI: 10.1016/j.jcat.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and particle size effects of Ag/α-Al2O3 catalysts for ethylene epoxidation

Abstract: a-AluminaCatalyst design Ethylene oxide Particle size effect a b s t r a c t Currently, for the industrial ethylene epoxidation a-alumina supported silver catalysts are the only catalyst of choice. We demonstrate a novel method to produce these catalysts with different silver particle sizes, but without changing other key parameters that may affect the catalytic performance such as support specific surface area or metal precursor. a-Alumina was impregnated with a silver oxalate solution, and was subsequently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 65 publications
6
67
2
Order By: Relevance
“…However,v arying the space velocity resulted in ac oncurrent decrease in EO selectivity (0.5-1.6 %) and increase in CO 2 selectivity (0.5-1.6 %) as space velocityw as decreased from % 500 000 cm 3 h À1 cm cat À3 to % 100 000 cm 3 h À1 cm cat À3 (Figure 10). There are two plausible reasons for the observed change in EO and CO 2 selectivity as space time increases:1 )the presenceo fasequential reaction pathway for EO combustion to CO 2 [19,23] under the reactionc onditions investigated, and/or 2) ac hange in the branching ratio of the common reactioni ntermediate with space time similart oa n observation by van den Reijen et al [57] wherein EO selectivity, measured on non-promoted Ag/a-Al 2 O 3 catalysts with silver particles izes between 20-200 nm at 453-543 K, decreases with increasing ethylene conversion.W en ote that only 0.6-1.8 %o fE Of ormed hast ou ndergo combustion to achieve the observed0 .5-1.6 %i ncrease in CO 2 selectivity,w hich is well below % 10 %E Oc ombustionm easured by Cant and Hall [19] on an unsupported silver sponge formulation without chlorine modification at 443 Ka nd ambient pressure.…”
Section: Kinetics For Ethylene Epoxidationsupporting
confidence: 67%
“…However,v arying the space velocity resulted in ac oncurrent decrease in EO selectivity (0.5-1.6 %) and increase in CO 2 selectivity (0.5-1.6 %) as space velocityw as decreased from % 500 000 cm 3 h À1 cm cat À3 to % 100 000 cm 3 h À1 cm cat À3 (Figure 10). There are two plausible reasons for the observed change in EO and CO 2 selectivity as space time increases:1 )the presenceo fasequential reaction pathway for EO combustion to CO 2 [19,23] under the reactionc onditions investigated, and/or 2) ac hange in the branching ratio of the common reactioni ntermediate with space time similart oa n observation by van den Reijen et al [57] wherein EO selectivity, measured on non-promoted Ag/a-Al 2 O 3 catalysts with silver particles izes between 20-200 nm at 453-543 K, decreases with increasing ethylene conversion.W en ote that only 0.6-1.8 %o fE Of ormed hast ou ndergo combustion to achieve the observed0 .5-1.6 %i ncrease in CO 2 selectivity,w hich is well below % 10 %E Oc ombustionm easured by Cant and Hall [19] on an unsupported silver sponge formulation without chlorine modification at 443 Ka nd ambient pressure.…”
Section: Kinetics For Ethylene Epoxidationsupporting
confidence: 67%
“…An alternative explanation would be that silver particles sinter to larger ones, which could be more active. Recently, van den Reijen et al 32 reported that the turnover frequency increases until the silver particle size is larger than 70 nm and thereafter the turnover frequency is constant. The silver time yield, defined as the moles of ethylene converted per gram of silver per s, had a maximum value over silver particles of approximately 60 nm size.…”
Section: Influence Of the Catalyst Preparation Methods On Conversion Amentioning
confidence: 99%
“…The silver time yield, defined as the moles of ethylene converted per gram of silver per s, had a maximum value over silver particles of approximately 60 nm size. 32 The selectivity to ethylene oxide was reported to be independent of silver particle size. However, the selectivity at a 2.8% ethylene conversion was about 50%, which is significantly lower than the selectivity we obtained.…”
Section: Influence Of the Catalyst Preparation Methods On Conversion Amentioning
confidence: 99%
“…Some evidence has been presented, which confirmed an increase of the EO selectivity with increasing Ag crystallite size . However, the effect of this parameter is still open to debate. Van den Reijen et al . reported selectivity values at constant ethylene conversion are independent on the Ag crystallite size.…”
Section: Introductionmentioning
confidence: 91%
“…Ethylene oxide (EO), industrially produced by the method of direct ethylene oxidation in air, is one of the most important chemical intermediates with the global capacity of 25 million tons per year in 2013. 1 The working catalyst for this reaction is silver (Ag) on an ultrapure aluminum oxide (Al 2 O 3 ) support with low specific surface area, normally below 2 m 2 /g. 2 The EO selectivity for catalysts without any promoter is around 50%, but adding 100-500 mg/kg of alkali or alkaline earth metals improves the selectivity significantly.…”
Section: Introductionmentioning
confidence: 99%